2020
DOI: 10.1037/pag0000456
|View full text |Cite
|
Sign up to set email alerts
|

The impact of age on the temporal compression of daily life events in episodic memory.

Abstract: While age differences in episodic memory are well documented, the impact of age on the structure of memories for real-world events has not been investigated in detail. Recent research has shown that the continuous flow of information that constitutes daily life events is compressed in episodic memory, such that the time needed to mentally replay an event is shorter than the actual event duration. To examine whether this process of temporal compression of prior experience in episodic memory is affected by aging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(35 citation statements)
references
References 66 publications
4
23
0
Order By: Relevance
“…It is important to note that the rate of event compression in episodic memory representations is not constant but varies substantially across events. For example, a consistent finding has been that events in which participants perform specific actions (e.g., buying a newspaper) are less compressed than events that only involve spatial navigation (e.g., going from one place to another with no action to perform except walking) (Folville et al, 2020;Jeunehomme et al, 2018Jeunehomme & D'Argembeau, 2019). In fact, the rate of temporal compression of an event in memory (i.e., the time needed to remember an event relative to the actual event duration) is inversely related to the Behavioural and neural evidence suggest that the formation of episodic memory units depends on the segmentation of the continuous stream of experience into events and sub-events (for review, see Radvansky & Zacks, 2017;Zacks, 2020).…”
Section: Compression Rates Are Variable and Depend On Event Segmentationmentioning
confidence: 98%
See 2 more Smart Citations
“…It is important to note that the rate of event compression in episodic memory representations is not constant but varies substantially across events. For example, a consistent finding has been that events in which participants perform specific actions (e.g., buying a newspaper) are less compressed than events that only involve spatial navigation (e.g., going from one place to another with no action to perform except walking) (Folville et al, 2020;Jeunehomme et al, 2018Jeunehomme & D'Argembeau, 2019). In fact, the rate of temporal compression of an event in memory (i.e., the time needed to remember an event relative to the actual event duration) is inversely related to the Behavioural and neural evidence suggest that the formation of episodic memory units depends on the segmentation of the continuous stream of experience into events and sub-events (for review, see Radvansky & Zacks, 2017;Zacks, 2020).…”
Section: Compression Rates Are Variable and Depend On Event Segmentationmentioning
confidence: 98%
“…For each event, participants were asked to mentally re-experience everything that happened in as much detail as possible, and the duration of their mental replay was measured. It was found that participants consistently spent less time remembering events compared to the actual event duration: on average, events were replayed about eight times faster than the actual event duration, with substantial variation in compression rates across events (see also Chen et al, 2017;Folville et al, 2020;.…”
Section: The Time To Remembermentioning
confidence: 99%
See 1 more Smart Citation
“…Older adults produced vividness ratings that were higher than young adults when remembering objects in a real-life setting, despite lower performance in remembering the spatio-temporal context of memory encoding (Mazurek et al, 2015). Also, older adults were found to report vividness ratings that were higher than those of young adults when remembering real-life activities (e.g., buying a beverage) while memory performance regarding the unfolding of the activity did not differ between age-groups (Folville, Jeunehomme et al, 2020). Results of that study further revealed that the intensity of memory vividness was predicted by the number of retrieved moments of experience when accomplishing the activity in young but not in older participants (Folville, Jeunehomme et al, 2020).…”
Section: Controlled Real-life Eventsmentioning
confidence: 75%
“…Also, older adults were found to report vividness ratings that were higher than those of young adults when remembering real-life activities (e.g., buying a beverage) while memory performance regarding the unfolding of the activity did not differ between age-groups (Folville, Jeunehomme et al, 2020). Results of that study further revealed that the intensity of memory vividness was predicted by the number of retrieved moments of experience when accomplishing the activity in young but not in older participants (Folville, Jeunehomme et al, 2020). Taken together, these findings provide evidence that older adults overestimate the intensity of their subjective vividness ratings and that these ratings seem to be unrelated to the quantity of retrieved memory details relative to those of young adults.…”
Section: Controlled Real-life Eventsmentioning
confidence: 85%